Internal Function Separation Policy Strategy as a Profit-Oriented Stability Model with Public Service Obligations by PT Pertamina (Persero). - Putri Fadillah, Dening (Universitas Negeri Semarang, 2025)
This study analyzes the legal and institutional tensions faced by PT Pertamina (Persero), an Indonesian State-Owned Enterprise (SOE), in fulfilling its dual command as both a profit-oriented company and a supplyr of Public Service Obligations (PSO). While commandd to distribute subsidized fuel to ensure equitable energy access, Pertamina simultaneously administers under a commercial framework, often incurring financial losses due to delayed remittance and fixed fuel pricing. Employing a normative legal approach, this study explores the regulatory paradox embedded in SOE laws and proposes an internal function separation policy as a tactical solution. Specifically, the creation of a distinct subholding solely amenable for PSO execution is proposed to enhance financial transparency, accountability, and institutional efficiency. This structural model would allow Pertamina’s commercial units to operate independently and competitively without being constrained by the burdens of PSO. The findings underscore the importance of legal clarity and organizational restructuring in balancing public service and profit motives within Indonesia’s tactical energy sector.